2004
DOI: 10.1002/cncr.20749
|View full text |Cite
|
Sign up to set email alerts
|

Original and reviewed nuclear grading according to the Fuhrman system

Abstract: BACKGROUNDThe objective of the current study was to evaluate the reproducibility of the Fuhrman nuclear grading system as well as its independent predictive value in a series of patients with conventional renal cell carcinoma (RCC).METHODSThe authors selected 388 patients who had undergone surgical treatment for conventional RCC between 1986 and 2000. Pathology slides from the selected patients were reviewed by a single pathologist, who reassigned a Fuhrman nuclear grade and assessed the presence of tumor necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…However, this drawback is minimized because studies have shown that Grades I and II tumors have a similar prognosis and that there is limited benefit in distinguishing them. [20212235] Another limitation is that the maximum nuclear size in the slide cannot distinguish Grade III from Grade IV tumors. This limitation is expected since Grade IV is determined by the morphology of the nuclei, and not just their size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this drawback is minimized because studies have shown that Grades I and II tumors have a similar prognosis and that there is limited benefit in distinguishing them. [20212235] Another limitation is that the maximum nuclear size in the slide cannot distinguish Grade III from Grade IV tumors. This limitation is expected since Grade IV is determined by the morphology of the nuclei, and not just their size.…”
Section: Discussionmentioning
confidence: 99%
“…We selected only three cases for Grade I because of its rarity (5-10%) among clear cell RCC cases. [102021]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(16, 49–51). Despite this, the value of this system in assessment of prognosis has been questioned (17, 19). Several studies have found that the Fuhrman grading system has prognostic significance only when the data are grouped (e.g.…”
Section: Isup Grading Classificationmentioning
confidence: 99%
“…Subsequently, the prognostic value of the Fuhrman nuclear grading system has well been recognized. However, the interobserver reproducibility is not considered to be satisfactory because of the complexity of the four-tiered grading system [26][27][28]. In the present Fig.…”
Section: Discussionmentioning
confidence: 93%